A comparative study of the perceptions of Austria-Hungary and Serbia in British newspapers during the July crisis of 1914 - Irving, Sonja (University of Ottawa (Canada), 2008)
This paper adopts a political and class-based approach to examine three different British newspapers, The Times of London, The Manchester Guardian, and The Daily Herald in terms of their treatment of Austria-Hungary and Serbia in the month prior to the First World War. It questions how a newspaper's particular bias affects the way it discusses a topic, disseminates news, and relates with its audience. It examines the influence a newspaper has on shaping public opinion concerning friendly and enemy nations in the lead up to a war. At the same time this paper also examines how a newspaper's class and political background determines the level of support the paper demonstrates for war or for pacifism.
Keywords: History, European.; Journalism.; History, Modern.